Pedal machine powered by human energy 'bicycle generator' / Wan Abdul Malek Wan Sulaiman - Wan Sulaiman, Wan Abdul Malek (2009)
The purpose of this project is to design the pedal machine powered by human energy to convert from mechanical power into electrical power [1] using alternator which directly connected to the bicycle's rim. Alternator is a generator that can generate a voltage as its pulley rotates [2]. Through cycling action, it produces energy which is turned into the electricity necessary to charge the battery. The battery plugs into a power inverter [3] then supply and deliver a consistent power to the electrical devices. The project also capable to help the cyclist to maintain the health which burnt the user's calories [4].